2005
DOI: 10.1002/dmrr.583
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of nutritionally induced diabetes by rosiglitazone in the gerbil Psammomys obesus

Abstract: These data indicate that the skeletal muscle is not the primary target of RG action, whereas the preservation of the insulin secretory capacity and the prevention of degenerative beta cell vacuolization in spite of persisting insulin resistance appear to be the basis for the anti-hyperglycaemic effect of RG in Psammomys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Hefetz and colleagues also reported no change in the total lipid content in skeletal muscle from diabetic P. obesus following rosiglitazone treatment, although they did not examine the size distribution of the lipid droplets [40]. Interestingly, microscopy analysis of pancreatic sections revealed that rosiglitazone prevented the decrease in insulin immunostaining induced by the high energy diet and accelerated β-cell proliferation (measured by BrdU incorporation into nuclei) [40]. Based on these observations, Hefetz et al concluded that the major anti-diabetic action of rosiglitazone in P. obesus was by preventing the deterioration of pancreatic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hefetz and colleagues also reported no change in the total lipid content in skeletal muscle from diabetic P. obesus following rosiglitazone treatment, although they did not examine the size distribution of the lipid droplets [40]. Interestingly, microscopy analysis of pancreatic sections revealed that rosiglitazone prevented the decrease in insulin immunostaining induced by the high energy diet and accelerated β-cell proliferation (measured by BrdU incorporation into nuclei) [40]. Based on these observations, Hefetz et al concluded that the major anti-diabetic action of rosiglitazone in P. obesus was by preventing the deterioration of pancreatic function.…”
Section: Discussionmentioning
confidence: 99%
“…Here we provide evidence to suggest that rosiglitazone treatment results in a reduction in lipid droplet size in skeletal muscle without a significant change in total IMCL. Hefetz and colleagues also reported no change in the total lipid content in skeletal muscle from diabetic P. obesus following rosiglitazone treatment, although they did not examine the size distribution of the lipid droplets [40]. Interestingly, microscopy analysis of pancreatic sections revealed that rosiglitazone prevented the decrease in insulin immunostaining induced by the high energy diet and accelerated β-cell proliferation (measured by BrdU incorporation into nuclei) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism in peripheral tissues was not the primary target of the beneficial effect of rosiglitazone, but rosiglitazone prevented the damage to pancreatic ␤-cells and loss of insulin, thus enabling insulin secretion to compensate for the peripheral insulin resistance (Hefetz et al 2006). Marquie and coworkers (1997) studied the oral agent S15261 (3-[2-[2-[4-[2-[␣-fluorenyl acetyl amino ethyl] enzoylosy] ethyl amino]1-methoxy ethyl] trifluoromethylbenzene), which also prevented the ␤-cell lesion in the HE diet-maintained Psammomys.…”
Section: Psammomys As a Model For Testing Antihyperglycemic Drugsmentioning
confidence: 98%
“…Another mechanism that might be involved in our study is based on the anti-oxidative activity of CBD [13,23], that very likely prevents beta cell destruction in the HE fed Psammomys. Vanadyl sulfate and rosiglitazone have also been found to be effective in preventing hyperglycemia and hyperinsulinemia [24,25], while nicotine treatment [26] caused decrease in food intake and body weight. An antidiabetic effect was also obtained by G protein kinase analogs [27] and electroacupuncture [28].…”
Section: Open Accessmentioning
confidence: 99%